Meningkatkan Hasil Belajar Pembagian Bilangan Dua Angka Menggunakan Media Puzzle Pada Siswa Kelas III SDN 24 Ampenan - Astuti, Wahyu Tina; Zain, Moh. Irawan; Thalha, Thalha (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
The aim of this research is to improve teacher performance in the learning process of dividing two-digit numbers using puzzle media so as to improve student learning outcomes. In this research, researchers used two cycles of Classroom Action Research (PTK). Each cycle consists of four stages, namely: planning, implementation/observation, and reflection. The target of this research was class III students at SDN 24 Ampenan. To analyze data to improve learning outcomes for dividing two-digit numbers using puzzle media, researchers used a quantitative approach and the research subjects were all class III students at SDN 24 Ampenan. The data collection methods used are teacher activity observation data, student activity observation data and student learning outcome data. Test data on student learning outcomes were analyzed based on the percentage of individual and classical learning completion and then explained descriptively. The research success indicator for teacher activity, student activity and student learning outcomes is 80%. The research results showed an increase in the percentage of teacher and student activity in cycle I and cycle II. Teacher activity increased by 11.10%, namely from 77.23% in cycle I to 88.83% in cycle II. Meanwhile, student activity increased by 9.66%, namely from 73.86% in cycle I to 83.52% in cycle II. The learning outcomes obtained by class III students at SDN 24 Ampenan have increased. Students' classical learning mastery increased by 20.84%, namely from 66.66% in cycle I to 87.50% in cycle II. Based on the results obtained, it can be concluded that the use of puzzle media can increase student activity and learning outcomes.